Peran Perusahaan Jasa sebagai Wujud Standarisasi Kelayakan Jasa Pengamanan Bidang Satpam (Studi Pada PT. Bawar Sakti Indonesia, Medan) - Nurul Hayati Panjaitan; Nurbaiti Nurbaiti (Jurnal Ilmiah Universitas Batanghari Jambi, 2023)
The increasing number of criminal cases and the growing development of the Usama Security Service Agency or security service providers in Indonesia are seen as opportunities by PT. Bawar Sakti Indonesia, which later established a security service provider. The purpose of this study was to determine the role of service companies as a form of standardization of the feasibility of security services in the security sector at PT. Bawar Sakti Indonesia. The method used is descriptive-qualitative research method, descriptive analysis method used by researchers is to provide an overview of the role of service companies in realizing security standardization. The data source consists of. articles, encyclopedias, newspapers, magazines, websites, and other academic studies related to this research. PT. Bawar Sakti Indonesia is able to convince company partners and give satisfaction to outsourcing users. In addition, armed with education from PT. Bawar Sakti Indonesia, the selected security guard also provides services in the form of suggestions, considerations or opinions and assists in the management of methods and procedures to protect an object.